THE INFLUENCE OF FACILITIES AND SERVICE QUALITY ON USER SATISFACTION OF COMPUTER LINE TRANSPORTATION SERVICES DEPARTEMENT OF CIKARANG –KAMPUNG BANDAN - Jamaludin, Agus; Yuningsih, Sri Sri; Anita, Tri; Susanto, Rudy (JABE (Journal of Applied Business and Economic), 2025)
This study evaluates the impact of facilities and service quality on user satisfaction with the Jabodetabek Commuter Line Train on the Cikarang-Kampung Bandan route. A quantitative approach was used, with 98 respondents selected through accidental sampling. Data analysis involved multiple linear regression, resulting in the equation: Y = 8,458 + 0,134X1 + 0,716 X2. The key findings are as follows: The tvalue for facilities (tcount = 11,807) is significantly higher than the critical tvalue (ttable = 1,985), leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). This indicates that facilities positively affect consumer satisfaction with the Jabodetabek Commuter Line Train. The tvalue for service quality (tcount = 14,752) also exceeds the critical tvalue (ttable = 1,985), resulting in the rejection of Ho and acceptance of Ha. This demonstrates a significant effect of service quality on consumer satisfaction. The Fvalue (Fcount = 109,856) is greater than the critical Fvalue (Ftable = 3,09), confirming the rejection of the null hypothesis. This shows that both facility and service quality significantly impact consumer satisfaction with rail transportation services on this route